How achievement of a stroke care pathway is associated with functional outcome after stroke: a national, register-based study - Elin Bergh; Torunn Askim; Ole Morten Rønning; Stian Lydersen; Hild Fjaertoft; Bente Thommessen (BMC Health Services Research)
Abstract Background Care pathways are introduced to ensure adherence to treatment guidelines for several patient groups. In the present study, we aimed to evaluate whether the achievement of key objectives within the recently implemented Norwegian stroke care pathway (SCP) was associated with functional outcome 3 months after stroke and to identify the characteristics of patients who achieved the recommended goals. Methods We conducted a register-based study with data from the Norwegian Stroke Registry (NSR). Patients who were registered with acute stroke in 2019, one year after the SCP was introduced, were included. The functional outcome at 3 months was compared between ‘achievement’ and ‘non-achievement’ patients. The modified Rankin scale (mRS) was used to measure functional outcome at 3 months post-stroke, functional independence was defined as an mRS score of 0–2. Results Among 2730 patients without missing data on achievement criteria, 272 (10%) were in the achievement group. The probability of being independent at 3 months post-stroke was significantly greater in the achievement group than in the non-achievement group (odds ratio (OR) 1.35, 95% CI 1.01 to 1.79, p = 0.043). However, subsequent sensitivity analyses did not replicate these findings, showing an average proportion of achievers of 7.2% (average odds ratios 1.12, 95% CI 0.88 to 1.45, p > 0.05). “Achievers” had better pre-stroke function, less likelihood of living alone, more severe strokes upon admission, and in addition, higher thrombolysis rates compared to “non-achievers.” Conclusion We concluded that in the early phase after the SCP was implemented, between 7% and 10% reached goal achievement. The estimated association between achievement and independence 3 months post-stroke was significant in the primary analysis, but lost significance in sensitivity analyses.